A fine cup of coffee - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Persuading the coffee world that East African coffees have a high quality and special taste is, in short, what the new East African Fine Coffee Association (EAFCA) aims to do. Low prices for normal coffees and higher ones for high quality coffee,...